Pengaruh Orientasi Kewirausahaan, Orientasi Pasar, Dan Inovasi Terhadap Kinerja UMKM Di Jakarta Barat - Martiano Dusy charlesman; Dwi Astuti (CV. ITTC INDONESIA, 2025)
MSMEs have an important role in the national economy. The growth of MSMEs in Indonesia has also increased from year to year. However, in running MSMEs, there are several difficulties or challenges and obstacles. The application of entrepreneurial orientation, market orientation and innovation can improve business performance and survive in the market. Therefore, it is important for MSME owners and/or managers to be able to implement this. This research aims to determine the influence of entrepreneurial orientation, market orientation and innovation on the performance of MSMEs. The samples used were 60 samples and were selected using the purposive sampling method. The questionnaire was used in this research as a research instrument in obtaining information from respondents. Data was processed using outer model analysis and inner model analysis on SmartPLS 4 software. The results of the research showed that entrepreneurial orientation and market orientation had a positive and insignificant effect on the performance of MSMEs. Meanwhile, innovation has a positive and significant effect on the performance of MSMEs.